2018
DOI: 10.1080/07352166.2018.1439339
|View full text |Cite
|
Sign up to set email alerts
|

Economic incentives and settlement intentions of rural migrants: Evidence from China

Abstract: Based on a large, nationwide, household-level survey data set collected in 2014, this article investigates the effect of economic incentives on the destination choices of Chinese new-generation rural migrants. Empirical results show that economic incentives have a significant positive impact on the probability of rural migrants' urban settlement intentions but with a diminishing marginal effect. We also find that the marginal effect of economic incentives on rural migrants' urban settlement decreases with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 42 publications
4
62
0
Order By: Relevance
“…Notably, the above conclusions are generally based on different kinds of survey data, and the definitions of "settlement intention" vary across studies. For instance, some scholars captured migrants' settlement intention through the question, "Do you want to live in the host city for more than 5 years" (Chen & Wang, 2019;Liu et al, 2018;Xie & Chen, 2018), while other research was based on the question, "Do you want to permanently settle in the host city" (Liu et al, 2017;Tao, 2017;Xing & Zhang, 2017). However, in the context of the weakened effect of the hukou system and the growing importance of homeownership, these two questions may produce different responses.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the above conclusions are generally based on different kinds of survey data, and the definitions of "settlement intention" vary across studies. For instance, some scholars captured migrants' settlement intention through the question, "Do you want to live in the host city for more than 5 years" (Chen & Wang, 2019;Liu et al, 2018;Xie & Chen, 2018), while other research was based on the question, "Do you want to permanently settle in the host city" (Liu et al, 2017;Tao, 2017;Xing & Zhang, 2017). However, in the context of the weakened effect of the hukou system and the growing importance of homeownership, these two questions may produce different responses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on migrants’ location choices regarding settlement intentions in urban areas has investigated the demographic characteristics of migrants (such as age, marital status, educational level), family factors (such as family size), economic factors (such as income level), and social factors (such as the characteristics of employment and social security) [ 19 , 20 , 21 , 22 , 23 ]. In addition to the above factors, air pollution has become one of the most significant health risks faced by urban residents around the world and, to a certain degree, influences the settlement intentions of migrants.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Chen and Wang (2019), for example, suggested that compared to highly educated rural migrants, rural migrants with less education were more sensitive to economic incentives-defined as the individual-specific income ratio between the host city and the hometown of migrant-when making decisions about permanent settlement in the host cities. A possible explanation is that rural migrants with less education tend to focus on short-run economic returns when they make settlement decisions, whereas migrants with higher educational attainment often have other considerations such as career opportunities and urban amenity features of the city (Chen & Wang, 2019;Zhu & Chen, 2010). Similar to education, income level of rural migrants has been found to be positively related to their preference for urban settlement.…”
Section: Literature Reviewmentioning
confidence: 99%